Workload, Fatigue, Family Conflict: Impact on Outpatient Medical Workers in Sidoarjo: Beban Kerja, Kelelahan, dan Konflik Keluarga: Dampak pada Tenaga Medis Rawat Jalan di Sidoarjo selama Pandemi Covid-19 - Aulya Oktaviona; Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2022)
This research study aimed to analyze and explain the condition of outpatient medical personnel during the COVID-19 pandemic at a Type D Hospital in Sidoarjo. The study focused on the increasing number of COVID-19 cases among patients and the occurrence of infections among non-medical employees. A quantitative approach was employed, utilizing an interval-level data collection method through observation, questionnaire distribution, and a saturated sample technique involving outpatient medical personnel. The study findings revealed that workload and work fatigue had a positive and significant impact on the performance of medical personnel. Additionally, the level of family conflict was found to have a positive effect on their performance. These results highlight the crucial factors influencing the performance of outpatient medical personnel during the pandemic, emphasizing the need for support and interventions to optimize their well-being and effectiveness in managing the ongoing crisis. Highlights: Workload and work fatigue significantly impact the performance of medical personnel during the Covid-19 pandemic. The level of family conflict influences the performance of outpatient medical workers. Understanding the effects of workload, work fatigue, and family conflict is crucial for supporting and optimizing the well-being of medical personnel during the pandemic. Keywords: Workload, Work Fatigue, Family Conflict, Outpatient Medical Workers, Covid-19.